English Teacher’s Strategy in English Teaching Learning at the Fourth Grade of SD Negeri Kowel 3 Pamekasan in 2013 Curriculum - Aini, Safi; Azizah, Siti (Institut Agama Islam Negeri Madura, 2019)
English is not a core curriculum for elementary school based on the new Curriculum (2013 Curriculum). However, SDN Kowel 3 Pamekasan, is an elementary school that has implemented the 2013 curriculum since 2013 and has taught English to their students. This research tries to analyze about how does the English teacher formulate the strategy in English teaching-learning and how is the implementation of it while English is not one of Core Curriculum in 2013 Curriculum at the fourth grade of SDN Kowel 3 Pamekasan. This research is qualitative descriptive research. Interview, observation, and documentation were utilized to collect the data. The result shows that the English teacher used the previous curriculum, School-Based Curriculum (SBC), as the basis of the English teaching-learning process when the subject is not in the 2013 curriculum. In this case, the school changes the position of English from an extra curriculum into a local curriculum. Moreover, the English teacher develops the lesson plan from the English material book following School-Based Curriculum format which is different from the lesson plan format of 2013 Curriculum. While the implementation is the English teacher commonly used Audio Lingual Method (ALM) through repetition drill at the beginning of the class.